Pentoxifylline immunomodulation in the treatment of experimental chronic pulmonary paracoccidioidomycosis (2015)
ABSTRACT : Background: Pentoxifylline (PTX) is a methylxanthine compound with immunomodulatory and antifibrotic properties. The simultaneous use of PTX and antifungal therapy (itraconazole) has previously been evaluated in anexperimental model of pulmonary paracoccidioidomycosis (PCM), a systemic fungal disease caused by the fungus Paracoccidioides brasiliensis (Pb) and characterized by chronic inflammation and lung fibrosis that appears even after a successful course of antifungal therapy. The results revealed prompt and statistically significant reductions in inflammation and fibrosis when compared to itraconazole alone. However, the effect of monotherapy with PTX on the host response to PCM has not been well-documented. Our aim was to determine the effect of PTX on the course of pulmonary lesions and on the local immune response. Results: At the middle and end of treatment, the Pb-infected-PTX-treated mice exhibited significant reductions in lung density compared to the Pb-infected-non-treated mice as assessed by the quantification of Hounsfield units on high-resolution computed tomography (HRCT) (p <0.05 by Kruskal-Wallis test); additionally, at the end of therapy, the lung areas involved in the inflammatory reactions were only 3 vs. 22 %, respectively, by histomorphometry (p <0.05 by Mann–Whitney test), and this reduction was associated with a lower fungal burden and limited collagen increment in the pulmonary lesions. PTX treatment restored the levels of IFN-γ, MIP-1β, and IL-3 that had been down-regulated by Pb infection. Additionally, IL-12p70, IL-10, IL-13, and eotaxin were significantly increased, whereas Regulated upon Activation, Normal T cell Expressed and Secreted (RANTES) levels were decreased in the lungs of the Pb-infected-PTX-treated mice compared to the non-treated group. Conclusions/significance: This study showed that PTX therapy administered at an “early” stage of granulomatous inflammation controlled the progress of the PCM by diminishing the pulmonary inflammation and the fungal burden and avoiding the appearance of collagen deposits in the pulmonary lesions.